Synthesis and spectroscopic characterisation of a combinatorial library based on the fungal natural product 3-chloro-4-hydroxyphenylacetamide - Davis, Rohan A (Magnetic resonance in chemistry : MRC, 2007)
Copyright (c) 2007 John Wiley & Sons, Ltd.